Battles and capitals - Shuhei Kitamura; Nils-Petter Lagerlöf (Osaka University, Institute of Social and Economic Research (ISER), 2025)
The location of cities is linked to access to trade, but security also matters, in particular for capitals. Here we document this phenomenon, and explore its implications, in the context of Europe's Great Power era. First we show that Great Power battles tend to occur in shortest-distance corridors between belligerent powers' capitals, except where those corridors are intercepted by seas, mountains, and marshes. Then we show that capitals locate closer to each other when they have more of these types of geography between them. Finally, we show that city pairs are less likely to belong to the same state if they have more of this geography between them, allowing us to use geography to predict the territorial size and shape of Europe's Great Powers. In sum, our results suggest that terrain which slows down military incursions makes capitals safer, allowing them to locate closer to each other; given all capitals' locations, the surrounding geography then shapes the associated state territories.
Keywords: F52; H56; N43; N90; 330; Conflict; battles; state fragmentation; cities